Integrative Therapy Combining Chinese Herbal Medicines With Conventional Treatment Reduces the Risk of Cardiovascular Disease Among Patients With Systemic Lupus Erythematosus: A Retrospective Population-Based Cohort Study - Yu, Han-Hua; Hsieh, Chia-Jung (Frontiers in Pharmacology, 2021)
Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease that involves multiple systems and organs. Advanced conventional treatment does not appear to markedly reduce the risk of cardiovascular disease (CVD) among patients with SLE. Chinese medicine is a complementary and alternative medicine system, and some SLE patients in Taiwan also use Chinese herbal medicines (CHMs). Thus, we aimed to investigate whether integrative therapy combining CHMs with conventional therapy reduces the risk of CVD among patients with SLE. We performed a 12-year population-based retrospective cohort study using the “Systemic Lupus Erythematosus Health Database” of the National Health Insurance Research Database (NHIRD) in Taiwan. Patients newly diagnosed with SLE between 2004 and 2013 were divided into CHM and non-CHM groups and followed up until the end of 2015. We applied 1:1 individual matching by age, gender, and year of being newly diagnosed with SLE; accordingly, 2751 patients were included in both CHM and non-CHM groups after matching. We applied the Cox proportional hazard regression model to determine the risk of CVD in relation to CHM use. During the follow-up period, 407 patients in the CHM group and 469 patients in the non-CHM group developed CVD, with incidence rates of 337 and 422 per 10,000 person-years, respectively. The Cox proportional hazards model demonstrated a significantly decreased risk of CVD among SLE patients using CHMs (adjusted HR: 0.83; 95% CI 0.73-0.95; p = 0.008). Further analyses of different types of CVDs also showed a significantly decreased risk of ischemic stroke in the CHM group (adjusted HR: 0.74; 95% CI 0.57-0.97; p = 0.032). Among the frequently used single herbs and polyherbal formulas, Shu-Jing-Huo-Xue-Tang was associated with a significantly decreased risk of CVD (adjusted HR: 0.76; 95% CI 0.58-0.99; p = 0.041). In conclusion, CHM use reduced the risk of CVD among patients with SLE in Taiwan. Further randomized studies may be needed to determine the definite causal relationship between CHM use and its protective effects against CVD among patients with SLE.